2000
DOI: 10.1007/s001250051567
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced intercellular adhesion molecule-1 (ICAM-1) expression through an osmotic effect in rat mesangial cells is PKC-NF-ϰB-dependent

Abstract: AbstractsAims/hypothesis. Infiltration of mononuclear cells and glomerular enlargement accompanied by glomerular cell proliferation are very early characteristics of the pathophysiology of diabetes. To clarify the mechanism of early diabetic nephropathy, we measured [ 3 H]-thymidine incorporation and cell numbers to show the influence of a high ambient glucose concentration and the osmotic effect on rat mesangial cell proliferation. We also measured the effect of high glucose on the expression of intercellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
97
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 23 publications
8
97
2
2
Order By: Relevance
“…The previous studies have shown that TGF-β1 results in transient proliferation of rats GMCs, followed by growth inhibition (Park et al, 2000;Drummond and Mauer, 2002), and similar results were also observed in our previous study (Rho et al, 2004). In contrast, TGF-β1 inhibits the proliferation of human and mouse GMCs which were cultured under serumfree condition (Stephenson et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…The previous studies have shown that TGF-β1 results in transient proliferation of rats GMCs, followed by growth inhibition (Park et al, 2000;Drummond and Mauer, 2002), and similar results were also observed in our previous study (Rho et al, 2004). In contrast, TGF-β1 inhibits the proliferation of human and mouse GMCs which were cultured under serumfree condition (Stephenson et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…5) Oxidative stress has been documented to increase ICAM-1 expression (30). 6) Osmotic agents upregulate ICAM-1 expression in rat mesangial cells (31) and in human umbilical vein endothelial cells (32). Our results showed that the infiltration of macrophages into the glomeruli was lower in diabetic ICAM-1 Ϫ/Ϫ mice compared with diabetic ICAM-1 ϩ/ϩ mice (reduction rate 78.5%), suggesting that ICAM-1 is a critical molecule for the infiltration of macrophages into glomeruli in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 66%
“…Here, the authors found that betaine (trimethylglycine), a natural specific type of zwitterion, known to improve visual acuity, has antioxidant properties and inhibits pathological neovascularization of human retinal microvascular endothelial cells exposed to high glucose levels, by attenuating ROS production, and subsequently suppressing both the VEGF receptor (VEGFR)-2 signaling pathway and VEGF production [3]. Betaine was, here, reported to act on the hyperosmolar component of hyperglycemia [4], a biophysical mechanism known to contribute to the development of microvascular disease in diabetes [5][6][7]. Thus, betaine would act on one pathway leading from hyperglycemia to microangiopathy.…”
Section: Introductionmentioning
confidence: 99%